CORRUPT PRACTICES IN UZBEK UNIVERSITIES AND INSTITUTIONAL APPROACHES TO OVERCOMING THEM - Максимова Умидахон Дилбаровна (Ecomind Press, 2025)
Corruption in higher education institutions in Uzbekistan is one of the most acute problems hindering the formation of high-quality human capital. This article analyzes the forms of its manifestation, from bribery at exams and buying grades to nepotism and administrative abuse. Particular attention is paid to systemic causes, including low teachers' salaries, archaic governance models and weak public control. Comprehensive measures aimed at eradicating corruption are proposed: digitalization of educational processes, increasing transparency, improving the social status of the teaching staff and the formation of legal awareness of students. The author comes to the conclusion that the fight against corruption in universities is a key condition for the sustainable development of the country and the training of competitive specialists.
Keywords: Corruption, higher education, academic integrity, digitalization, reforms, nepotism, legal consciousness.